2013
DOI: 10.1097/dad.0b013e31829ce220
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Mucinosis Associated With Nonlymphoid Skin Conditions

Abstract: Background: Follicular mucinosis coexisting with lymphoproliferative disorders has been thoroughly debated. However, it has been rarely reported in association with inflammatory disorders.Methods: Thirteen cases have been retrieved, and those with cutaneous lymphoma or alopecia mucinosa were excluded.Results: It was found follicular mucinosis in the setting of squamous cell carcinoma, seborrheic keratosis, simple prurigo, acne vulgaris, dextrometorphan-induced phototoxicity, polymorphous light eruption (2 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Mir-Bonafé et al reported on a series of thirteen cases with FM associated with nonlymphoid skin conditions, mainly inflammatory disorders, emphasizing that FM is a reactive histological pattern that can be seen unrelatedly to CTCL. 1 In our study of FM in a population of cancer center patients, FM was unrelated to CTCL in 51% of the cases and none of these 46 patients developed CTCL after a mean follow-up of 4.3 years. Our findings support the concept that FM should not be considered as a variant of MF or a precursor stage of CTCL as previously suggested.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Mir-Bonafé et al reported on a series of thirteen cases with FM associated with nonlymphoid skin conditions, mainly inflammatory disorders, emphasizing that FM is a reactive histological pattern that can be seen unrelatedly to CTCL. 1 In our study of FM in a population of cancer center patients, FM was unrelated to CTCL in 51% of the cases and none of these 46 patients developed CTCL after a mean follow-up of 4.3 years. Our findings support the concept that FM should not be considered as a variant of MF or a precursor stage of CTCL as previously suggested.…”
Section: Resultsmentioning
confidence: 62%
“…Clinically, FM presents as follicular prominence, acneiform eruption and focal hair loss. FM in association with various systemic conditions including hematological malignancies, hematopoietic stem cell transplantation (HSCT), and other malignant and benign skin disorders 1 has been occasionally reported. However, it is typically reported in the context of cutaneous T-cell lymphomas (CTCL), specifically folliculotropic mycosis fungoides (MF).…”
Section: Introductionmentioning
confidence: 99%
“…3 En este contexto, ante un hallazgo histopatológico de mucinosis folicular, el dermatólogo debe evaluar la posibilidad de que su paciente tenga una entidad clínicamente definida, cuya fisiopatología o comportamiento biológico explique el hallazgo de mucinosis folicular en la biopsia. Algunas de estas entidades pueden ser: linfoma cutáneo de células T; micosis fungoide principalmente, leucemia linfocítica crónica, linfoma cutáneo de células B, leucemia mieloide aguda y crónica, macroglobulinemia, linfosarcomas y entidades de carácter inflamatorio o infeccioso como prúrigo simple, erupción solar polimorfa, lupus discoide, vasculitis asociada a medicamentos, demodecidosis 4 foliculitis eosinofílica asociada a VIH, leishmaniasis, lepra, sarcoidosis, alopecia areata, liquen simple, liquen plano, liquen estriado, acné, entre otras. 5 Quienes han sostenido esta discusión en la literatura, ya sea a favor o en contra de la mucinosis folicular como hallazgo histológico sin ser una entidad per se, proponen que estos pacientes deben seguirse estrechamente.…”
Section: Primer Escenariounclassified
“…5 Quienes han sostenido esta discusión en la literatura, ya sea a favor o en contra de la mucinosis folicular como hallazgo histológico sin ser una entidad per se, proponen que estos pacientes deben seguirse estrechamente. 3,4,6 Segundo escenario Mucinosis folicular como entidad per se. Este escenario correspondería a las denominadas formas idiopáticas o benignas, que son las más frecuentes, y se presentan como mucinosis folicular aguda localizada; se manifiestan como una o dos lesiones en cabeza y cuero cabelludo, en niños y adultos jóvenes.…”
Section: Primer Escenariounclassified
“…We suspected a drug‐induced FM secondary to infliximab. Drug‐induced FM has been described in association with imatinib, oxcarbamazepine, captopril, and dextromethorphan . The onset of FM after several months of infliximab, resolution following the withdrawal of therapy, and evidence of infliximab‐induced ANA conversion suggested a fundamental role of pharmacologic TNF‐alpha blockade.…”
Section: Introductionmentioning
confidence: 99%